2017
DOI: 10.1104/pp.16.01555
|View full text |Cite
|
Sign up to set email alerts
|

Rice Sucrose Partitioning Mediated by a Putative Pectin Methyltransferase and Homogalacturonan Methylesterification

Abstract: Homogalacturonan (HG) is the main component of pectins. HG methylesterification has recently emerged as a key determinant controlling cell attachment, organ formation, and phyllotaxy. However, whether and how HG methylesterification affects intercellular metabolite transport has rarely been reported. Here, we identified and characterized knockout mutants of the rice () gene encoding a putative pectin methyltransferase. mutants exhibit a remarkable decrease in the degree of methylesterification of HG in the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…When cells differentiate, they need to communicate closely with surrounding cells (Kepinski, 2006). In the QUA2/TSD2 deletion mutant, abnormalities in cell adhesion in the hypocotyl occurred, indicating the possibility of an abnormality in intercellular communication (Qu et al, 2016;Xu et al, 2017). In the present study, the complement test confirmed the recovery of abnormal morphology.…”
Section: Ospmt16 Affects Pistil Morphogenesissupporting
confidence: 72%
“…When cells differentiate, they need to communicate closely with surrounding cells (Kepinski, 2006). In the QUA2/TSD2 deletion mutant, abnormalities in cell adhesion in the hypocotyl occurred, indicating the possibility of an abnormality in intercellular communication (Qu et al, 2016;Xu et al, 2017). In the present study, the complement test confirmed the recovery of abnormal morphology.…”
Section: Ospmt16 Affects Pistil Morphogenesissupporting
confidence: 72%
“…Because de-methyl-esterified HG produced by PMEs can have contrasting mechanical effects on the wall depending on how the de-methyl-esterification occurs (Hocq et al, 2017 ), it is currently unknown how these PMEs alter the biomechanics of the guard cell wall. Because PMEs enzymatically remove methyl groups from the pectin backbone in the apoplast whereas putative PMTs are localized in the Golgi (Mouille et al, 2007 ; Kim et al, 2015 ; Xu et al, 2017 ; Figure 2 ), it is unlikely that a de-methylesterification/methylesterification cycle occurs on pectins in the apoplast during fast and reversible stomatal movements in mature guard cells. Instead, the de-methyl-esterification patterns of HG generated by PME activity and their mechanical effects on the guard cell wall are more likely established during guard cell morphogenesis (Movie S1 ).…”
Section: Post-synthesis Modification Of the Guard Cell Wallmentioning
confidence: 99%
“…Mutants for another allele of QUA2, osu1, are more sensitive to imbalanced C/N conditions, suggesting that QUA2 is also a key modulator of carbon and nitrogen nutrient balance during plant development (Gao et al, 2008). In addition, mutants of a rice (Oryza sativa) putative ortholog of AtQUA2 show altered wall composition and developmental defects (Qu et al, 2016;Xu et al, 2017). OsQUA2 shares high sequence similarity with AtQUA2, and mutation of OsQUA2 results in reduced HG methylesterification in culm-sieve element and root cell walls, affecting sucrose transport and root development, respectively (Qu et al, 2016;Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mutants of a rice (Oryza sativa) putative ortholog of AtQUA2 show altered wall composition and developmental defects (Qu et al, 2016;Xu et al, 2017). OsQUA2 shares high sequence similarity with AtQUA2, and mutation of OsQUA2 results in reduced HG methylesterification in culm-sieve element and root cell walls, affecting sucrose transport and root development, respectively (Qu et al, 2016;Xu et al, 2018). QUASIMODO3 (QUA3), another putative HG methyltransferase, influences pectin methylesterification and regulates cell wall biosynthesis in Arabidopsis suspension-cultured cells (Miao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%